THE INTERNATIONAL RESPONSIBILITIES OF DEVELOPED COUNTRIES IN ADAPTATION TO AND MITIGATION OF CLIMATE CHANGE: AN ETHICAL MANDATE - M. D. Fite (BRICS Law Journal, 2018)
This article asserts three propositions. First, climate change and/or global warming has (and will continue to have) qualitative differences in its nature and impact on rich and poor countries, thus demonstrating the imperative of adaptation to and mitigation of its effects. Second, the current international environmental regime is insufficient for sensible global distributive justice. What is more, in the absence of an adequate regime the world continues to ignore fundamental ethical issues and the immediate needs of climate-vulnerable countries. Third, the effective preservation of the environment necessitates that developed countries bear the (ethical) responsibility for meeting the costs associated with climate change, and urgently and unremittingly discharge their obligation to assist developing and/or least developed countries in adapting to and mitigating the impact of global warming.